Hydrologic Correlates of Reproductive Success in the Alligator Gar. (16th June 2020) - Smith, Nathan G.; Buckmeier, David L.; Daugherty, Daniel J.; Bennett, Daniel L.; Sakaris, Peter C.; Robertson, Clinton R.
Abstract: Previous work relating adult age data to historic hydrology indicated that strong year‐classes of Alligator Gar Atractosteus spatula were rare, tied to major flooding events, and linked to the inundation and connectivity of floodplain habitats. Although spawning habitat suitability criteria have been correlated with successful recruitment in Texas Alligator Gar populations, direct evaluation of recruitment documenting young‐of‐the‐year (age‐0) presence or abundance has not been reported. To specify conditions associated with successful spawning and recruitment of Alligator Gar, we sampled for age‐0 fish monthly from May to July 2013–2017 in the Trinity River and from May to July 2015–2017 in Choke Canyon Reservoir. Suitability criteria predicted strong year‐classes in 2015 and 2016 for the Trinity River and in 2015 for Choke Canyon Reservoir; the predictions were confirmed by the presence of abundant age‐0 Alligator Gar in those systems and years. Hatch dates of juvenile Alligator Gar were estimated from otoliths and compared to corresponding environmental and hydrologic conditions. Hatch date analyses indicated a protracted spawning duration in 2015 associated with extended widespread flooding and a narrower range of spawning dates in 2016. Due to rapid growth and variable gear efficacy relative to fish size, multiple gears were required to assess the full size range of age‐0 Alligator Gar. A standardized sampling framework that included visual searching and floating mini‐fyke nets effectively sampled age‐0 Alligator Gar from 15 to 650 mm TL. We recommend a two‐tiered approach for predicting and monitoring Alligator Gar recruitment. First, the monitoring of hydrology and the application of suitability criteria can provide an early predictor of potential Alligator Gar reproductive success. If conditions are favorable for spawning, then sampling for age‐0 Alligator Gar can confirm recruitment and can give an indication of the spatial extent (visual searching) and relative abundance (visual searching and/or mini‐fyke nets) of successful reproduction.